EMPOWERED AND COURAGEOUS WOMAN: THE POWER OF CHANGING EDUCATION CHAOS IN THE FILM RAATCHASI - Nur Fitria, Tira (International Journal of English Learning and Applied Linguistics (IJELAL), 2023)
This research describes the acts of empowering and encouraging women of the main character (Geetha Rani) in the film Raatchasi. This research is descriptive qualitative. The Raathacsi film is about a headmistress (principal) converting a poorly run school into one of the best in the state. Geeta Rani is the principal of an unauthorized government school in a secluded area of southern Tamil Nadu. Geetha Rani, the newly appointed headmistress of a government school, fights back against mismanagement and failings of the educational system. She must deal with misbehaving students, unmotivated teachers, and a lack of established rules and regulations. She did her utmost to instruct students and supervise teachers to be professional. Her abrupt strict and progressive policies are not well received. Her earnest efforts will bring about some much-needed reform and improve the academic standards in the process such as conducting discipline in the school area, changing the school atmosphere, changing students’ behavior, organizing a program for students’ talents, engaging students to compete, changing teachers’ performance, approaching students’ parents, and renovating the school’s building. In this film, Geeta Rani makes a favorable impression as a confident woman. This character and film are excellent for empowering and encouraging women.